The Influence of Somatic, Auditory, Visual, Intellectual (SAVI) Approach Assisted by Flipbook on the Mathematical Understanding Ability of Elementary School Students - Illahi, Rumai Syah Septiani Nuur; Rahayu, Puji; Hikmatunisa, Nenden Permas (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This study addresses the issue of low mathematical understanding among fifth-grade elementary students, emphasizing the necessity for innovative instructional methods that cater to diverse learning styles. The purpose of this research is to evaluate the effectiveness of the Somatic, Auditory, Visual, Intellectual (SAVI) approach, enhanced with flipbook media, in improving students’ mathematical comprehension compared to the Contextual Teaching and Learning (CTL) model. Utilizing a quasi-experimental design with a nonequivalent control group structure, students were divided into an experimental group (SAVI approach) and a control group (CTL approach). Data were collected through pretest and posttest evaluations to assess learning gains. The findings revealed that students exposed to the SAVI approach achieved a higher average posttest score (74.25) than those taught using the CTL model (64.00), with statistical significance indicated by a p-value of 0.018. This study concludes that employing the SAVI method with flipbook support significantly enhances students' mathematical understanding compared to conventional contextual approaches. The implications of these results underscore the potential of integrating multisensory strategies and interactive media in elementary mathematics instruction to improve student learning outcomes. Further research is recommended to explore the application of the SAVI approach across various subjects and educational contexts to strengthen and broaden these findings.